Radiographic patterns and associations of osteoarthritis of the hip. Issue 10 (October 1992) - Ledingham, J; Dawson, S; Preston, B; Milligan, G; Doherty, M
Abstract : A number of patterns of osteoarthritis of the hip are described, though studies are conflicting with respect to the frequency of such patterns and their associations. Two hundred and eleven patients (133 women, 78 men; mean age 66 years, range 29-86) referred to hospital with osteoarthritis of the hip were studied. Involvement was unilateral in 108 (51%) and bilateral in 89 (42%); 14 (7%) had undergone arthroplasty and were presenting with osteoarthritis hips). Sixty one per cent of hips had severe, 28% moderate, and 11% mild changes (Kellgren grade). Superior pole migration occurred in 82% (46% superolateral, 25% intermediate, 11% superomedial), medial/axial migration occurred in only 8%, and in 10% the pattern was indeterminate. In bilateral osteoarthritis of the hip the pattern was generally symmetrical. Superomedial and medial/axial patterns were proportionately more common in women, whereas superlateral osteoarthritis predominated in men. No association was found between multiple clinical nodes, radiographic polyarticular interphalangeal or first carpometacarpal osteoarthritis and any migration pattern. Any interphalangeal osteoarthritis was negatively associated with medial migration. Only 40% of hips could be categorised as hypertrophic or atrophic; chondrocalcinosis at any site was associated with atrophic osteoarthritis; no associations were seen with Forestier's disease. This large survey confirms the association between chondrocalcinosis and atrophic osteoarthritis of the hip. Importantly it suggests that gender, rather than associated osteoarthritis at other sites, is a major determinant of the pattern of osteoarthritis of the hip.